Age-conditioned differences in parents’ attitudes towards compulsory vaccination - Kałucka, Sylwia Katarzyna; Łopata, Ewelina (Family Medicine & Primary Care Review, 2016)
Background. Vaccinations are the most effective tool in preventing serious infectious diseases. However, due to an increase in negative opinions on immunization, more and more parents avoid mandatory vaccinations each year. Objectives. The aim of the study was to compare the attitude towards vaccinations of two generations of parents. Material and methods. The study involved 140 individuals with children up to the age of 7 (78 people) and between the ages of 18–19 (62 people). It was carried out among the patients of two community health care centers, using the author’s proprietary survey. Results. In the group of young parents having a small child, only 71% of them wanted compulsory vaccinations, as opposed to older parents, among which 94% wished to maintain continue this (p 0.001), the same group, more often than the older generation, expressed opinions concerning the inefficiency of vaccines, too large amount of vaccines in the current immunization program, no need to vaccinate children and the possibility of replacing it through a healthy lifestyle and natural methods of immunization. Conclusions . The young generation of parents increasingly ignores the recommendations for an obligatory vaccination schedule. Parents of those children who were of age were less likely to question the efficacy and sense of mandatory vaccinations. Information booklets should be given out to parents with a child reporting for vaccination.